Use of a virtual learning environment for training in maxillofacial emergencies: impact on the knowledge and attitudes of staff in accident and emergency departments. Issue 2 (February 2016) - Elledge, Ross; McAleer, Sean; Thakar, Meera; Begum, Fathema; Singhota, Sanjeet; Grew, Nicholas
Abstract: Many graduates will take up junior roles in accident and emergency (A&E) departments to which a large proportion of patients present with facial injuries caused by interpersonal violence. However, it is widely recognised that undergraduates and postgraduates have few opportunities for training in oral and maxillofacial surgery. We aimed to assess the impact of a specifically designed maxillofacial emergencies virtual learning environment (VLE) on the knowledge and confidence of junior doctors in two A&E departments. They were given free access to the VLE for one month, and were asked to complete multiple choice questions and to rate their confidence to deal with 10 common situations on visual analogue scales (VAS) at baseline and one month after training. A total of 29 doctors agreed to pilot the website, 21 (72%) completed both sets of questions, and 18 (62%) completed both VAS assessments. The mean (SD) multiple choice score improved from 10 (2.52) to 13 (3.56) out of a maximum of 20 (p=0.004) and the mean (SD) VAS improved from 29.2 (19.2) mm to 45.7 (16.6) mm out of a maximum of 100 mm (p=0.007). This was a small pilot study with limited numbers, but it showed improvements in the knowledge of maxillofacial emergencies and in confidence, although the latter remained low. Further work is needed to examine how these brief educational interventions affect the attitudes of frontline staff to maxillofacial emergencies.